Intraestadual migration in Rio Grande do Norte: study from Nmr-interior and interior-Nmr flows - Silva, Priscila de Souza; Queiroz, Silvana Nunes de (Universidade Estadual de Campinas, 2020)
The main objective of this work is to analyze the recent evolution of intra-state migration in Rio Grande do Norte, from the flows between the Metropolitan Region of Natal (RMN) and the interior of the state, and the interior and the Metropolitan Region of Natal, during the five-year periods of 1995/2000 and 2005/2010. For this, the main source of information is the samples of microdata from the Demographic Census 2000 and 2010 provided by the Brazilian Institute of Geography and Statistics (IBGE). The main results show a greater dynamization of migrations within the state itself and an intensification of the trend of the metropolis-interior flow, with a significant decrease in the negative balance of the interior in relation to NMR. In terms of municipalities, the highlight was Mossoró, which presented the highest volume of immigrants and emigrants to and from the NMR, and the greatest reduction in the negative migratory balance, between the periods of 1995/2000 and 2005/2010. On the other hand, in the NMR there was a decline in population gains coming from the interior and a significant increase in emigration to the respective area, showing a reduction in the attractiveness, notably from the capital (Natal), which has a greater positive migratory balance and volume of inflows and With the interregnum under analysis, Natal significantly reduces the positive balance, as a result of a set of negative externalities that, associated with greater dynamization of the interior, especially medium-sized cities, boost the maintenance of the population. inland, as well as reemigration, deconcentrating the population of the NMR.